Correlation Between Spicy Food Consumption, Academic Stress, and Boarding School Environment and the Risk of GERD Among Students at Darul Falah Islamic Boarding School - Destiana Dwi Lestari; Diding Kelana Setiadi; Ria Inriyana (Jurnal Vocational Nursing Sciences (VNUS), 2026)
This study explores the relationship between spicy food consumption, academic stress, and the pesantren environment with the risk of Gastroesophageal Reflux Disease (GERD) among students at Pondok Pesantren Darul Falah. GERD is a chronic digestive disorder caused by acid reflux and is prevalent among adolescents with specific lifestyle factors in an Islamic boarding school setting. A cross-sectional quantitative design was employed with 194 participants aged 15-18 years, using validated questionnaires to assess dietary habits, stress levels, environmental perceptions, and GERD symptoms. Spearman’s rank correlation analysis showed significant correlations between spicy food consumption (r = 0.338, p < 0.001), academic stress (r = 0.146, p < 0.042), and unfavorable perceptions of the pesantren environment (r = -0.170, p = 0.018) with GERD risk. These results indicate that dietary, psychological, and environmental factors collectively contribute to the prevalence of GERD in this population. The study concludes that preventive strategies in pesantren should integrate nutrition education, stress management, and environmental improvements to effectively reduce GERD incidence and promote student health.